Factors that contribute to improve organization performance: key performance indicator (KPI) At TDM Berhad / Siti Nur Amirah Mohd Khalid - Mohd Khalid, Siti Nur Amirah
This study was conducted to review new implemented Key Performance Indicator (KPI) and investigate which factors contribute to improve organizational performance at TDM Berhad. There are five independent variables used include employees’ talent, employee relation, training and development, mission, vision, value and strategy, and organization and structure. Meanwhile, the dependent variable used was organizational performance. To conduct this study, researcher used quantitative method by distributing a set of questionnaires to 60 respondents and cluster sampling method was chosen due to small number of populations which required 60 sample of respondents. The finding revealed that training and development, vision, mission, value and strategy and organization and structure have significant relationship with organizational performance. Therefore, in order to increase organization performance at TDM Berhad, some recommendation is suggested such as well-documented training policy and giving more opportunity to employees for training and development, enhance two ways communication between manager and employees to help employees clearly understand what to be achieved and all staffs should be clearly understand the job description.